2021
DOI: 10.48550/arxiv.2109.00568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bridging the gap between mesoscopic and molecular models of solid/liquid interfaces out-of-equilibrium

Abstract: Solid/liquid interfaces control various processes of technological relevance in the process industry and many fundamental physicochemical phenomena. This work examines the link between the atomistic description of mass transfer at solid/liquid interfaces out of equilibrium and the constitutive mass transfer equations typically used to model these processes at the mesoscale. In our analysis we discuss the microscopic inconsistencies apparent in simplified models of mass transfer whenever non-idealities dominate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Recently, we showed that surfaces catalyse the formation of large liquid-like NaCl clusters in solutions where the chemical potential is held constant in CmMD simulations. 80,81 Both the size and density of ions in the clusters were increased in the presence of graphite surfaces. Within the context of CNT, interfaces reduce the surface energies of emerging nuclei and therefore the thermodynamic barriers to nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that surfaces catalyse the formation of large liquid-like NaCl clusters in solutions where the chemical potential is held constant in CmMD simulations. 80,81 Both the size and density of ions in the clusters were increased in the presence of graphite surfaces. Within the context of CNT, interfaces reduce the surface energies of emerging nuclei and therefore the thermodynamic barriers to nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that surfaces catalyse the formation of large liquid-like NaCl clusters in solutions where the chemical potential is held constant in CµMD simulations. 80,81 Both the size and density of ions in the clusters were increased in the presence of graphite surfaces. Within the context of CNT, interfaces reduce the surface energies of emerging nuclei and therefore the thermodynamic barriers to nucleation.…”
Section: Markov State Modelmentioning
confidence: 99%